Working in private universities does emotional intelligence matter for job effectiveness - Ahmad Shah, Norliana; Saad, Mazni; Mohamad Mohan, Noor Malinda; Poniran, Halimi (Global Academic Excellence, 2018)
The recent trend has introduced the emotional quotient or intelligence (EQ) as the essential concepts to the psychology and management for academicians. EQ describes a person's ability to sense and respond appropriately to emotions. Thus, this paper seeks to examine the impact of EQ on private university lecturers’ job effectiveness. A primary goal is to explore the EQ of the private universities’ lecturers and examine how it predicts their job effectiveness beyond the ability. Quantitative analysis in the form of a survey was used in this study. A total of 20 private universities were listed and approached; however, only five universities agreed to participate. The cross-sectional data collection was done within a month, and the data obtained in the survey were analysed with the IBM-SPSS. The results showed that emotional intelligence has a significant impact on job effectiveness of the lecturers. However, only self-regulation and social skill are statistically significant, with selfregulation variable represents the strongest unique contribution to explain the job effectiveness. The findings of the study suggest that employees can apply their personal emotional experience into their work well. Also, it helps them to develop strong emotional bonding with those people associated with their work and leads to organizational performance. Hence, it is particularly imperative for a private university to use EQ to predict job effectiveness.